2015
DOI: 10.1038/leu.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Clofarabine salvage therapy before allogeneic hematopoietic stem cell transplantation in patients with relapsed or refractory AML: results of the BRIDGE trial

Abstract: In patients with relapsed or refractory (r/r) acute myeloid leukemia (AML), long-term disease control can only be achieved by allogeneic hematopoietic stem cell transplantation (HSCT). We studied the safety and efficacy of clofarabine-based salvage therapy. The study was designed as phase II, multicenter, intent-to-transplant (ITT) study. A total of 84 patients with r/r AML were enrolled. All patients received at least one cycle of CLARA (clofarabine 30 mg/m(2) and cytarabine 1 g/m(2), days 1-5). Chemo-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…To assess the potential clinical relevance of RRM1 inhibition in MM, we next examined the effect of the purine nucleoside antimetabolite CLO, an RRM1 inhibitor that is approved for the treatment of acute lymphocytic leukemia [2630], on MM cell lines (NCI-H929, MM.1S, MOLP-8, RPMI8226, OPM2, U266, and KMS-11). TP53-wild type cells (NCI-H929, MM.1S, and MOLP-8) were more sensitive to CLO treatment compared to TP53-mutant (RPMI8226, OPM2, and U266) or TP53-null (KMS-11) cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential clinical relevance of RRM1 inhibition in MM, we next examined the effect of the purine nucleoside antimetabolite CLO, an RRM1 inhibitor that is approved for the treatment of acute lymphocytic leukemia [2630], on MM cell lines (NCI-H929, MM.1S, MOLP-8, RPMI8226, OPM2, U266, and KMS-11). TP53-wild type cells (NCI-H929, MM.1S, and MOLP-8) were more sensitive to CLO treatment compared to TP53-mutant (RPMI8226, OPM2, and U266) or TP53-null (KMS-11) cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Clofarabine is a nextgeneration purine analog with significant antileukemic activity, particulary in relapsed AML and acute lymphoblastic leukemia. [14][15][16][17][18] We found that a RIC regimen combining clofarabine, bulsulfan and anti-thymocyte globulin was safe, with a 1-year NRM rate of 6%, and allowed efficient disease control in AML patients in CR. 19 Thus, the use of clofarabine as an alternative to fludarabine in the setting of RIC allogeneic SCT appears to be very attractive.…”
Section: Introductionmentioning
confidence: 89%
“…[1][2][3] Previous retrospective and small phase-II studies suggested utility of clofarabine as 'bridge' to transplant in patients with active disease when followed by a reduced intensity conditioning regimen. [4][5][6][7] We sought to confirm these findings by examining survival following a clofarabine bridge to HSCT. Clofarabine is currently approved in the United States for the treatment of acute lymphoblastic leukemia (ALL) in children and has been used off label for the treatment of ALL and AML in adults.…”
mentioning
confidence: 83%